Seleksi, Karakterisasi Morfologi, dan Identifikasi Aktinobakteri Penghasil Mananase Asal Hutan Tanah Jambi untuk Produksi Mananoligosakarida - Rahayu Wulan; Rika Indri Astuti; Yaya Rukayadi; Sri Estuningsih; Anja Meryandini (Institut Pertanian Bogor, 2022)
As the world's largest producer of crude palm oil, Indonesia also produces high palm kernel cake (PKC) by-products. PKC has a high mannan content, so it can be used to produce prebiotic mannan-oligosaccharides (MOS). Enzymatic MOS production can be carried out using actinobacterial mannanase's microbiological approach. The HJ45B-1 isolate was the best isolate, with a peak enzyme production of 0,338 U/mL on the 10th day of incubation. The mannanase enzyme was stable in storage at 27°C. MOS production using 1% PKC substrate produced MOS with the best degree of polymerization (2-4) with incubation for 1-3 hours. Morphological characteristics and molecular identification based on the 16S rRNA gene indicated that the HJ45B-1 isolate was Streptomyces spp. Keywords: actinobacteria, mannanase, mannan-oligosaccharides, palm kernel cake, Streptomyces